Neonatal Morbidity and Mortality in Advanced Aged Mothers—Maternal Age Is Not an Independent Risk Factor for Infants Born Very Preterm - Nourkami-Tutdibi, Nasenien; Tutdibi, Erol; Faas, Theresa; Wagenpfeil, Gudrun; Draper, Elizabeth S.; Johnson, Samantha; Cuttini, Marina; Rafei, Rym El; Seppänen, Anna-Veera; Mazela, Jan; Maier, Rolf Felix; Nuytten, Alexandra; et al. (Frontiers in Pediatrics, 2021)
BACKGROUND: As childbearing is postponed in developed countries, maternal age (MA) has increased over decades with an increasing number of pregnancies between age 35-39 and beyond. The aim of the study was to determine the influence of advanced (AMA) and very advanced maternal age (vAMA) on morbidity and mortality of very preterm (VPT) infants. METHODS: This was a population-based cohort study including infants from the “Effective Perinatal Intensive Care in Europe” (EPICE) cohort. The EPICE database contains data of 10329 VPT infants of 8928 mothers, including stillbirths and terminations of pregnancy. Births occurred in 19 regions in 11 European countries. The study included 7607 live born infants without severe congenital anomalies. The principal exposure variable was MA at delivery. Infants were divided into three groups (reference 18-34 years, AMA 35-39 years and very(v) AMA ≥40 years). Infant mortality was defined as in-hospital death before discharge home or into long-term paediatric care. The secondary outcome included a composite of mortality and/or any one of the following major neonatal morbidities: 1) moderate-to-severe bronchopulmonary dysplasia; 2) severe brain injury defined as intraventricular haemorrhage and/or cystic periventricular leukomalacia; 3) severe retinopathy of prematurity; and 4) severe necrotizing enterocolitis. RESULTS: There was no significant difference between MA groups regarding the use of surfactant therapy, postnatal corticosteroids, rate of neonatal sepsis or PDA that needed pharmacological or surgical intervention. Infants of AMA/vAMA mothers required significantly less mechanical ventilation during NICU stay than infants born to non-AMA mothers, but there was no significant difference in length of mechanical ventilation and after stratification by gestational age group. Adverse neonatal outcomes in VPT infants born to AMA/vAMA mothers did not differ from infants born to mothers below the age of 35. Maternal age showed no influence on mortality in live-born VPT infants. CONCLUSION: Although AMA/vAMA mothers encountered greater pregnancy risk, the mortality and morbidity of VPT infants was independent of maternal age.